Postnatal Rosiglitazone Administration to Neonatal Rat Pups Does Not Alter the Young Adult Metabolic Phenotype - Truong, Nghia C. (S. Karger AG, 2012)
BACKGROUND: Rosiglitazone (RGZ), a peroxisome proliferator-activated receptor-γ (PPARγ) agonist, significantly enhances lung maturation without affecting blood biochemical and metabolic profiles in the newborn period. However, whether this exposure to RGZ in neonatal life alters the adult metabolic phenotype is not known. OBJECTIVE: To determine the effects of early postnatal administration of RGZ on the young adult metabolic phenotype. METHODS: Newborn rat pups were administered either saline or RGZ for the first 7 days of life. At 11–14 weeks, glucose and insulin tolerance tests and deuterium labeling were performed. Blood and tissues were analyzed for various metabolic parameters. RESULTS: Overall, there was no effect of early postnatal RGZ administration on young adult body weight, glucose and insulin tolerance, plasma cholesterol and triglyceride profiles, insulin, glucagon, cardiac troponin, fatty acid synthesis, or tissue adipogenic differentiation. CONCLUSIONS: Treatment with RGZ in early neonatal life does not alter later developmental metabolic programming or lead to an altered metabolic phenotype in the young adult, further re-enforcing the safety of PPARγ agonists as a novel lung-protective strategy.